Cardiovascular Effects of Pharmacological Targeting of Sphingosine Kinase 1. Issue 2 (February 2020) - Józefczuk, Ewelina; Nosalski, Ryszard; Saju, Blessy; Crespo, Eva; Szczepaniak, Piotr; Guzik, Tomasz Jan; Siedlinski, Mateusz
Abstract : High blood pressure is a risk factor for cardiovascular diseases. Ang II (angiotensin II), a key pro-hypertensive hormone, mediates target organ consequences such as endothelial dysfunction and cardiac hypertrophy. S1P (sphingosine-1-phosphate), produced by Sphk1 (sphingosine kinase 1), plays a pivotal role in the pathogenesis of hypertension and downstream organ damage, as it controls vascular tone and regulates cardiac remodeling. Accordingly, we aimed to examine if pharmacological inhibition of Sphk1 using selective inhibitor PF543 can represent a useful vasoprotective and cardioprotective anti-hypertensive strategy in vivo. PF543 was administered intraperitoneally throughout a 14-day Ang II-infusion in C57BL6/J male mice. Pharmacological inhibition of Sphk1 improved endothelial function of arteries of hypertensive mice that could be mediated via decrease in eNOS (endothelial nitric oxide synthase) phosphorylation at T495. This effect was independent of blood pressure. Importantly, PF543 also reduced cardiac hypertrophy (heart to body weight ratio, 5.6±0.2 versus 6.4±0.1 versus 5.9±0.2 mg/g; P <0.05 for Sham, Ang II+placebo, and Ang II+PF543-treated mice, respectively). Mass spectrometry revealed that PF543 elevated cardiac sphingosine, that is, Sphk1 substrate, content in vivo. Mechanistically, RNA-Seq indicated a decreased expression of cardiac genes involved in actin/integrin organization, S1pr1 signaling, and tissue remodeling. Indeed, downregulation of Rock1 (Rho-associated coiled-coil containing protein kinase 1), Stat3 (signal transducer and activator of transcription 3), PKC (protein kinase C), and ERK1/2 (extracellular signal-regulated kinases 1/2) level/phosphorylation by PF543 was observed. In summary, pharmacological inhibition of Sphk1 partially protects against Ang II–induced cardiac hypertrophy and endothelial dysfunction. Therefore, it may represent a promising target for harnessing residual cardiovascular risk in hypertension. Abstract : Supplemental Digital Content is available in the text.